Eco-friendly synthesis of ZnO nanoparticles using Magnolia macrophylla and their photocatalytic applications: Photodegradation of methylene blue - Ulker, Gorkem; Ozen, Sedef; Gorduk, Semih (ELSEVIER, 2026)
In this study, the photocatalytic performance of ZnO nanoparticles synthesized via a green synthesis approach was investigated for the removal of methylene blue organic dye. ZnO nanoparticles were synthesized using Magnolia macrophylla and were characterized by FT-IR, XRD, UV-DRS, and SEM-EDX analyses. XRD results confirmed that the nanoparticles possess crystallinity of 99.51 % and 56.87 nm crystal size. UV-DRS analysis showed good agreement with pure ZnO reported in the literature, confirming successful synthesis, and the band gap energy was determined to be 2.87 eV. Photocatalytic activity was evaluated through methylene blue degradation under UV and visible light irradiation. Under UV light, 99.84 % degradation was achieved within 30 min using 0.3 g of ZnO synthesized in an ethanol medium at pH 14, while ZnO synthesized in distilled water reached 98.91 % degradation in 120 min under the same conditions. Under visible light, the highest degradation efficiency (97.51 %) was obtained within 60 min for ZnO synthesized in an ethanol medium at pH 14. Overall, the results demonstrate that green-synthesized ZnO nanoparticles are effective photocatalysts for wastewater treatment containing organic dyes.
Keywords: Green synthesis; Magnolia macrophylla; Photodegradation; Methylene blue; ZnO nanoparticles; OXIDE NANOPARTICLES; WASTE-WATER; BIOSYNTHESIS; FUNGI; METAL; Chemistry